Mythological Creatures in the Samogitian Daily Discourse of the 2nd Half of the 20th Century - Pajėdienė, Jūratė (Vilnius University Open Series, 2021)
The article presents an overview of the contexts and functions of using the names of mythological creatures found in the Samogitian daily discourse of the second half of the twentieth century, paying attention to the dual – rational or subconscious – nature of naming a mythological creature. The overview is based on the material provided by the Samogitian dialect dictionaries (see Aleksandravičius 2011, Vanagienė 2014–2015) and by the collection of authentic Samogitian speech texts (see Girdenis 1996). Special attention is paid to the types of expressions formed with the name of the devil. In the Samogitian daily discourse the name of the devil (or the name of another mythological creature subordinate to the devil) is used not only in cursing but also to show one’s ignorance (the type of constructions ‘the devil knows what’ is very popular), to convey comparisons, epithets, to reinforce the meaning of certain words. The word vel’(n’)s ‘the devil’ and some of its synonyms are chosen as a distinctive, but quite common substitute for a personal name or are used as an address (addressing a person). Usually, such descriptions are related to a person’s energy and otherness or changes in his/her behaviour patterns.
Keywords: Samogitian daily discourse; names of mythological creatures; names of devil; euphemisms